2018
DOI: 10.1111/bjet.12674
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning and student cognition: A systematic review of PK‐12 research using Bloom’s Taxonomy

Abstract: The rise of mobile learning in schools during the past decade has led to promises about the power of mobile learning to extend and enhance student cognitive engagement. The purpose of this study was to examine trends to determine the cognitive level students are involved in within mobile learning activities. This systematic review involved an aggregated and configurative synthesis of PK‐12 mobile learning studies from 2010 to 16 and used Bloom’s Taxonomy as a theoretical framework for categorizing the cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 28 publications
5
32
0
Order By: Relevance
“…As expected, mobile learning design in outdoor settings is easier with science related subjects and not that self-evident and natural process with Languages. Our results are aligned with studies reported in Crompton et al (2018) literature review. The reason for the high percentage of lower level thinking skills in Languages might be due to considering students' level and skills in languages (Tyas et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As expected, mobile learning design in outdoor settings is easier with science related subjects and not that self-evident and natural process with Languages. Our results are aligned with studies reported in Crompton et al (2018) literature review. The reason for the high percentage of lower level thinking skills in Languages might be due to considering students' level and skills in languages (Tyas et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…In general terms, the results of our study are aligned for example with the studies by Cochrane and Antonczak (2014) and Crompton, Burke, and Lin’s (2018), who have reported that mobile learning designs remain rather traditional allowing learners to be passive consumers, often repeating typical classroom activities, thus bringing in hardly any innovation. In particular, the results of our study demonstrate that teacher created mobile learning scenarios are limited in terms of addressing higher levels of students’ cognitive processes (see Figure 2), making use of the power of authentic learning contexts (see Figure 3) and providing interdisciplinary learning experiences (see Figure 4).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PRISMA has been successfully employed in earlier educational studies, e.g. see the systematic review of Crompton, Burke, and Lin () or Sønderlund, Hughes and Smith (). Peer‐Reviewed Instructional Materials Online Database (PRIMO) was used for searching articles published in the past 10 years.…”
Section: Methodsmentioning
confidence: 99%
“…Faculty in engineering and technology departments across the United States subscribe to the concepts espoused in Bloom's taxonomy (Anderson & Sosniak, 1994; Bloom et al, 1956). This framework is used to shape curriculum, and provide educational activities that encourage student upper‐level cognitive activity (Crompton et al, 2019). The objective is to provide homework problems, classroom conversations and laboratory exercises that motivate the students to think beyond simple answers and solutions.…”
Section: Introductionmentioning
confidence: 99%